Está en la página 1de 4

x y1=x^2 y2=2-x 24

-5 25 7
-4 16 6
19
-3 9 5
-2 4 4 16
-1 1 3 14
0 0 2
1 1 1 9 9
2 4 0
3 9 -1 4 4 4
4 16 -2
5 25 -3 1 1
0
-1
-5 -4 -3 -2 -1 0 1 2

x y1=(x^2)-2 y2=x
-5 23 -5 20
-4 14 -4
-3 7 -3 15
-2 2 -2
-1 -1 -1
10
0 -2 0
1 -1 1
2 2 2 5
3 7 3
4 14 4 0
5 23 5 -5 -4 -3 -2 -1 0 1 2

-5

x y1=(x^2)-x y2=2 29
-5 30 2
-4 20 2 24
-3 12 2
-2 6 2 19
-1 2 2
14
0 0 2
1 0 2
9

-1
19

14

9
2 2 2
3 6 2
4
4 12 2
5 20 2 -1
-5 -4 -3 -2 -1 0 1
25
24

19

16
14
25
7
9 9

4 4

1 1
0
-1
-1 0 1 2 3 4 5

20

15

10 23
-5

0
-1 0 1 2 3 4 5

-5

29

24

19

14 30
2
9

-1
19

14 30
2
9

-1
-2 -1 0 1 2 3 4 5

Intereses relacionados